Kebijakan Non Penal dalam Menanggulangi Kekerasan Fisik Terhadap Perempuan (Studi Penelitian di Kantor Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Labuhanbatu) - Aulia, Paradina; Sitepu, Rajin (Universitas Ekasakti, 2023)
The protection of a just and civilized humanity can be planned with rational protection through non-penal policies in crime prevention efforts. Criminal policy aims to provide protection to society in order to realize people's happiness in living a healthy and refreshing cultural life. The purpose of this study is to describe and analyze efforts to overcome physical violence against women in Labuhanabatu Regency at the office of women's empowerment and child protection. The method used in this research is empirical research located in Labuhanbatu Regency, namely at the Labuhanbatu Regency (P2TP2A) unit. The results of this study are that it was found that the data on physical violence against women in Labuhanbatu Regency. Labuhanbatu is that in 2021 there were 3 cases and in 2022 it increased to 9 cases. The forms of violence that occur are in the form of beatings, slaps, kicks, jambakan, strangulation which result in bodily damage such as bruises, facial injuries. Activities to Prevent Physical Violence Against Women carried out by the P2TP2A Office of Labuhanbatu Regency are Socialization and counseling on